El sistema logístico como una herramienta en la gestión administrativa de la empresa comercializadora San Juan SAC, periodo 2023 - Montes Chavez, Ambar Manuela (2023)
The logistics system, as well as the administrative management, represent the set of actions that companies use to continue with the normal functioning of the operational activities that they develop in a certain period, and whose purpose is the desired performance and productivity for business management, and in this way, achieve the best results. The research has the title "The logistics system as a tool in the administrative management of the company Commercialized San Juan SAC, period 2023", its objective is to determine the relationship between the logistics system and administrative management in the company for said period. His study was of a quantitative type and a descriptive correlational design, where the survey was used as a technique and the questionnaire as an instrument for data collection, its validation was carried out through the judgment of three experts and its consistency was determined by means of the reliability test. which was applied to a sample made up of 96 workers. Finally, after processing and analyzing the data in the spss v25 statistical software, a high positive relationship was determined, which is supported by Spearman's Rho coefficient, which was 0.732 and the degree of significance at 0.000.